Effect of diversity distribution symmetry on global oscillations of networks of excitable units - Scialla, Stefano; Patriarca, Marco; Heinsalu, Els; Yamakou, Marius; Cartwright, Julyan H.E. (Physical Review E, 2025)
We show that the degree of symmetry of the diversity distribution is the key determinant of global oscillations in coupled networks of FitzHugh-Nagumo units, used as prototypical examples of excitable systems. In these ensembles, symmetric diversity reliably yields resonant collective oscillations - even when all units are individually excitable - whereas asymmetric diversity suppresses them. Two symmetry-based metrics predict the presence or absence of global oscillations from the distribution alone. A simple mean-field mechanism, corroborated by a minimal two-unit analysis, explains how symmetry creates a landscape that supports limit cycles. These results identify diversity distribution symmetry as a key mechanism for emergent synchronization in excitable media.
CRIS-Team Scopus Importer:2025-12-05